Genetic diversity in F2 segregating population of different commercial hybrids of tomato (Solanum lycopersicum L.) - Ghosh, KP; Islam, AKMA; Mian, MAK; Hossain, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 43-48